ANALISIS PENGENDALIAN INTERN ATAS PIUTANG TAK TERTAGIH PADA PT SINAR BINTANG ASIAPRIMA - Budi Tri Rahardjo, Ak., M.Ak., CA (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
This research was conducted with the aim to analyze the implementation of internal control system for bad debts, effective and efficient level of internal control over bad debts at PT Sinar Bintang Asiaprima.This research is a descriptive research. The data used are obtained from observation, interview, collect official document of company and compare between explanation of data and information obtained from PT Sinar Bintang Asiaprima with literature theories.Based on the results obtained in the internal control system of PT Sinar Bintang Asiaprima has not fulfilled the COSO component that is not yet have a written code of ethics, has not given a strict punishment to employees who commit fraud, has not done separation of tasks on the part of the treasury storage function and recording function, the financial statements are not audited by independent auditors, have not applied the principles of 5C (Caharacter, Capacity, Collateral, Capital, Condition) in crediting procedures, have not conducted supervision of employee performance, have not conducted direct monitoring and have not conducted periodic performance evaluation.Internal control over the bad debts in PT Sinar Bintang Asiaprima has not been effective and efficient because it is not fully in accordance with the five internal control components according to COSO. There is only one internal control component according to COSO that is Risk Assessment that has been suitable and has been implemented, while the four internal control components according to COSO that is Control Environment, Control Activities, Information and Communication, and Monitoring not all activities in internal control component implemented. The researcher recommends that PT Sinar Bintang Asiaprima make regulations and code of ethics in writing for employee to minimize risk of employees violating the code of ethics, to give strict punishment to employees who cheat, to separation of duties in the collection with the cashier as well as on the recording of sales with the delivery goods, financial statements audited by independent auditors on a regular basis, applying the 5C principle in crediting procedures, requiring customers to issue PO (Purchase Order) in every purchase, supervising employee performance, performing direct monitoring, and evaluating work through the Annual Meeting (RAT).